Implementation of Islamic Educational Management through Boarding-Based Student Development to Realize an Effective Madrasah - Iwan Irwandi; Devi Fatwanti; Encep Syarifudin; Eneng Muslihah; Siti Patimah (CV. Edujavare Publishing, 2026)
The development of education in Indonesia is experiencing increasing change and progress, particularly in Islamic-based educational institutions such as madrasas. This study aims to examine in-depth the governance of student development in a boarding school-based education model as an effort to realize an effective and superior Madrasah Aliyah Negeri 2 Tangerang. Using a descriptive qualitative approach, data were collected through in-depth interviews, non-participant observation, and documentation studies. The data analysis process followed the interactive framework of Miles, Huberman, and Saldana, which includes data condensation, data presentation, and drawing conclusions, with validity guaranteed through triangulation of sources and techniques. The research findings indicate that the implementation of managerial functions including planning, organizing, mobilizing, and supervising has been harmoniously integrated with the principles of school-based management. This synergy has been proven to create an educational ecosystem conducive to optimizing student potential. This managerial transformation has had a substantial impact on improving academic and non-academic achievements, strengthening students' disciplined, religious, and independent character, and strengthening the image and public trust in the institution. To ensure sustainable quality, this study recommends a comprehensive strategic approach to addressing managerial obstacles, particularly related to strengthening budget allocation, improving coordination, and developing the competencies of boarding school supervisors. Theoretically and practically, this research confirms the significance of transforming boarding school-based student development management in accelerating the achievement of highly competitive madrasahs